Hemoglobin Extracted From Perinereis aibuhitensis Acts as a Cell Culture Medium Supplement to Reduce Apoptosis - Huo, Qianyu; Liu, Jing; Cheng, You; Cao, Bin; Lei, Ming; Liu, Yunde (Frontiers in Marine Science, 2021)
The environmental oxygen concentration is a crucial factor affecting cell proliferation. Owing to the reversible binding property of hemoglobin to oxygen, it can be utilized to regulate the oxygen concentration in vitro and its ability to reduce apoptosis can be evaluated. In this study, a process comprising isolation, purification, and extraction was used to obtain hemoglobin from Perinereis aibuhitensis, a polychaete invertebrate. Extracts were separated and characterized using sodium dodecyl sulfate-polyacrylamide gel electrophoresis. Extract component identity was confirmed by matrix-assisted laser desorption time-of-flight mass spectrometry analysis, with the molecular weight determined as 412216.6875 Da. The oxygen carrying capacity of P. aibuhitensis hemoglobin was approximately comparable to that of human hemoglobin. P. aibuhitensis hemoglobin remarkably downregulated the apoptosis rate. Reactive oxygen species (ROS) assays confirmed the reduction in ROS production, enabling a better elucidation of the mechanism underlying the decrease in apoptosis. These results suggested that P. aibuhitensis hemoglobin is a natural oxygen carrier, that, owing to its low-cost and accessibility, can be considered a candidate culture medium supplement to reduce the apoptosis rate.